Management of Emergency Services in Bangladesh: A Study on Selected Tertiary Level Government Hospital - Amena Sultana Kakoli, Md. Anower Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The role of emergency department of a hospital and its services is immense important to the patients. Aim: To find out the management of the emergency services provided by the government hospital in Bangladesh. Method: The data were collected from 56 individual outpatients attending in emergency department of one of the tertiary level hospitals situated in the capital city of Bangladesh during 22th April to 3rd May 2012, following checklists and pre-structured questionnaire. Along with popular statistical tools and techniques, 0-4 Likert Scale Score was also used to measure the level of client satisfaction regarding the efficient management or quality services provided by the hospital. Results: The study shows that about 27% of the patients are not involved with any formal income activities, about 40% came to the hospital with surgical emergency, only 7% used ambulance to arrive at hospital and more than half of them (53.6%) were to come in the examination table through walking. In spite of emergency service, more than half of the patients were to waiting maximum 15 minutes after reaching the emergency department (ED). The Likert Scale clearly indicates that management services provided by SSMCH emergency is not appreciated by the all patients, which is really alarming for the health sector of the county. Practical Implication: The strength of health sector of a country as well as the popularity of a hospital mostly depends on the services provided by its emergency department. The findings will help the authority to improve the management of the services provided by the emergency department of hospitals in Bangladesh. Conclusion: Along with other measures, the government and concern authority should take necessary steps to ensure management of emergency services at all government hospitals across the country. Keywords: Emergency, Services, Management, Hospital and Tertiary Level.